Correlates of HIV-Positive Fathers’ Involvement in Prevention of Mother-to-child Transmission Programs in Northern Nigeria - Iliyasu, Zubairu; Galadanci, Hadiza S.; Muhammad, Bashir; Yadudu, Fatima Z.; Kwaku, Aminatu A.; Salihu, Hamisu M.; Aliyu, Muktar H. (Current HIV Research, 2020)
Background: The involvement of men in prevention of mother-to-child HIV transmission (PMTCT) programs could accelerate the elimination of vertical transmission. Yet, little research has focused on HIV-positive male partners. This study determined the predictors of male partners’ PMTCT knowledge and involvement in a tertiary hospital in northern Nigeria. Methods: A clinic-based sample of 401 HIV-positive male partners of women who delivered within 12 months prior were interviewed using structured questionnaires. PMTCT knowledge and involvement scores were computed. Adjusted odd ratios (AOR) for predictors were derived from multivariate logistic regression models. Results: The proportion of respondents with adequate PMTCT knowledge was 40.9%. Less than half (43.6%) of the respondents participated in PMTCT, with median involvement score of 2.00 (interquartile range, IQR = 0, 5.0). One quarter of respondents (25.7%, n =103) reported >1 sex partners, 10.5% consistently used condoms, and 20.7% had disclosed to all partners. Fathers’ involvement in PMTCT was predicted by paternal education (AOR = 0.30; 95% Confidence Interval (CI): 0.12-0.77, no formal vs. post-secondary), HIV-positive child (AOR = 3.85; 95%CI: 1.41-10.54, yes vs. no), treatment duration (AOR = 4.17; 95%CI: 1.67-10.41, ≤1 vs. ≥10 years), disclosure to partner(s) (AOR = 1.21; 95%CI: 1.15-3.52, ‘disclosed to all’ vs. ‘not disclosed’), condom use (AOR = 5.81; 95%CI: 3.07-11.0, always vs. never), and PMTCT knowledge (AOR = 0.62; 95%CI: 0.31-0.92, inadequate versus adequate). Conclusion: The involvement of fathers in HIV PMTCT programs was low and predicted by paternal education, HIV-positive child, duration of antiretroviral treatment, disclosure to partner, consistent condom use, and level of PMTCT knowledge. Our findings will inform the development of policies to increase male partner involvement in PMTCT in Nigeria.
Keywords: male partner involvement